Editorial: Oral Immune-Enhancing Research in Fish - Reyes-Lopez, F (Frontiers Media S.A., 2022)
[No abstract available]
Keywords: teleost fish model; Omics; probiotics-immunobiotics; disease enhancement; endobolome; holistic analysis; selective manipulation; microbiome